PEMIMPIN HUMAN CAPITAL 4.0 DAN KEPEMIMPINAN GLOBAL DI ERA MILENIAL - Tianggur Medi Napitupulu (Institut Agama Kristen Negeri Tarutung, 2020)
Leadership is a universal attribute that can be found practically in many situations and all walks of life that involves communities and various different types of culture. Within this context, a Leader has the most important role in the area of organization related leadership, with a task and role to determine the success and or failure of the organization he or she is leading. So the question that needs to be asked within this context is, what kind of Leader and leadership that is relevant in leading an organization in the XXI Century for the Millennial Generation? In order to answer this question, this article is given the title Human Capital 4.0 Leader and Global Leadership in the Millennial Era, outlines an idea that leadership and Leaders that is relevant for the Millennial Era is the type of leadership that gives an example of a Leader who is also an entrepreneur, have the qualification and understanding in the area of Human Capital 4.0, where these ideas will be discussed further within two main topics, which is: First, A Leader Who Also an Entrepreneur, and Two, Global Leadership and a Human Capital 4.0 Leader in the Millennial Era.BAHASA INDONESIA ABSTRAK: Kepemimpinan adalah gejala universal yang dapat ditemukan di segala tempat, dan semua waktu, dalam semua bentuk masyarakat dan kebudayaan. Dalam kaitan ini, Pemimpin memiliki tempat yang utama dalam kepemimpinan, dengan tugas dan peran yang menentukan keberhasilan atau kegagalan organisasi yang dipimpinnya. Dalam hubungan ini dipertanyakan, kepemimpinan dan Pemimpin macam apa dan macam bagaimana yang diperlukan dalam memimpin organisasi pada Abad XXI bagi Generasi Milenial? Menjawab pertanyaan dimaksud, tulisan yang berjudul Pemimpin Human Capital 4.0 dan Kepemimpinan Global di Era Milenial, mengetengahkan gagasan bahwa kepemimpinan dan Pemimpin yang dibutuhkan pada Era Milenial ini adalah kepemimpinan global dengan Pemimpin kompeten berjiwa entrepreneur, berkualifikasi Human Capital 4.0, yang dituangkan dalam dua pokok, yaitu: Pertama, Pemimpin Kompeten Berjiwa Entrepreneur; Kedua, Kepemimpinan Global dan Pemimpin Human Capital 4.0 dalam Era Milenial.Keywords: Leadership, Global Leadership, Leader, Entrepreneur, and Human Capital 4.0 Leader.